HYBRID GOVERNANCE IN INDONESIA’S NATION BRANDING: M4 WORLD CHAMPIONSHIP 2023 - Glory Yolanda Yahya; Listari Noviyanti; Desri Gunawan; Marisa Elsera; Hadli Lidya Rikayana (Intermestic: Journal of International Studies, 2026)
This study examines the dynamics of hybrid governance in Indonesia’s nation branding practices through the 2023 M4 World Championship. The global esports tournament was organized by Moonton as a multinational private company, while the Indonesian government acted as a facilitator through policy support, institutional legitimacy, and symbolic involvement. This study employed an interpretivist qualitative approach with a single-case study strategy. Data were collected from policy documents, official press releases, government statements, organizer publications, and credible media coverage. Previous studies still limited research that specifically analyzes the 2023 M4 World Championship as a global esports event organized by a multinational corporation from the perspective of hybrid governance. This study addresses that gap by examining how the interaction between state and private actors constructs nation branding practices in Indonesia within a hybrid governance structure. The findings show that Indonesia’s nation branding through M4 was formed within a hybrid governance configuration. Moonton controlled the operational and production aspects of the event, while the state utilized the event as a strategic platform to project Indonesia’s national image. Indonesia was represented through narratives and symbols emphasizing modernity, tourism, digital entertainment, and the creative economy. The novelty of this study lies in its use of hybrid governance theory to explain nation branding practices in global esports events managed primarily by multinational private actors. This research demonstrates that nation branding in the digital era is no longer fully state-led, but emerges through collaborative governance between governments and global corporations in transnational digital spaces.